Association of Obesity with Disease Severity Among Patients with Coronavirus Disease 2019. Issue 7 (12th June 2020) - Kalligeros, Markos; Shehadeh, Fadi; Mylona, Evangelia K.; Benitez, Gregorio; Beckwith, Curt G.; Chan, Philip A.; Mylonakis, Eleftherios
Abstract : Objective: The aim of this study was to explore the potential association of obesity and other chronic diseases with severe outcomes, such as intensive care unit (ICU) admission and invasive mechanical ventilation (IMV), in patients hospitalized with coronavirus disease 2019 (COVID‐19). Methods: This study analyzed a retrospective cohort of 103 patients hospitalized with COVID‐19. Demographic data, past medical history, and hospital course were collected and analyzed. A multivariate logistic regression analysis was implemented to examine associations. Results: From February 17 to April 5, 103 consecutive patients were hospitalized with COVID‐19. Among them, 44 patients (42.7%) were admitted to the ICU, and 29 (65.9%) required IMV. The prevalence of obesity was 47.5% (49 of 103). In a multivariate analysis, severe obesity (BMI ≥ 35 kg/m 2 ) was associated with ICU admission (adjusted odds ratio [aOR]: 5.39, 95% CI: 1.13‐25.64). Moreover, patients who required IMV were more likely to have had heart disease (aOR: 3.41, 95% CI: 1.05‐11.06), obesity (BMI = 30‐34.9 kg/m 2 ; aOR: 6.85, 95% CI: 1.05‐44.82), or severe obesity (BMI ≥ 35 kg/m 2 ; aOR: 9.99, 95% CI: 1.39‐71.69). Conclusions: In our analysis, severe obesity (BMI ≥ 35 kg/m 2 ) was associated with ICU admission, whereas history of heart disease and obesity (BMI ≥ 30 kg/m 2 ) were independently associated with the use of IMV. Increased vigilance and aggressive treatment of patients with obesity and COVID‐19 are warranted.